Pokemon adventures. 07 - Kusaka, Hidenori; Turnage, Bryant (Viz Media, 2021)
Contains a collection of graphic novel short stories that follow the adventures of Pokémon trainers. First, Ruby and Sapphire are shocked to discover that Archie and Maxie, the leaders of the evil Team Aqua and Team Magma, are controlling two Legendary Pokémon, Kyogre and Groudon. Then, Ruby and Sapphire learn about a surprising connection between the two of them that will change everything they thought they knew.